Epidemiological investigation of 673 patients who resorted to the emergency department for mild head trauma complaints (Annals of Medical Research, 2021)
Aim: Mild head trauma (MHT) or mild traumatic brain injury (MTBI) is an injury whose incidence is increasing in emergency services. This retrospective study carried out an epidemiological evaluation of patients with MHT, who underwent head computed tomography (HCT) with a 15-point score on the Glasgow Coma Scale (GCS).Material and Methods: This study retrospectively evaluated 673 patients with MHT, who were examined by the department of neurosurgery in the emergency department of Istinye University, Canakkale Anatolian Hospital between 2015 and 2019. The cases were evaluated because of age, gender, cause of trauma, HCT findings, duration of admission to the emergency department, and other body traumas associated with head trauma.Results: 390 (57.95%) patients were male, while 283 (42.05%) were female. The mean age and standard deviation were calculated as 23.72 ± 24.87 years. Of the 673 cases, 494 (73.40%) were admitted to the emergency department due to non-high falls. After trauma, 642 (95.39%) patients were admitted to the emergency department within the admitted to the emergency department within the first two hours after injury. 656 (97.48%) of the patients were treated in the emergency department. 105 (15.60%) patients had a scalp incision and underwent a small surgical procedure. The most common accompanying body trauma detected was that of the maxillofacial region in 26 (3.86%) patients. HCT pathology was detected in 20 (2.97%) patients. These pathologies included; 14 (2.08%) non-surgical intracerebral hemorrhage, 2 (0.30%) skull base fractures, 1 (0.15%) traumatic subdural hematoma, 1 (0.15%) traumatic epidural hematoma, 1 (0.15%) pneumocephalus and 1 (0.15%) cerebral edema.Conclusion: Head trauma is an important issue in this country. Brain CT may not be necessary in patients with a GCS score of 15. After a short observation, if patients live near the medical center, they can be sent home to return the next day for further evaluation.
Keywords: Epidemiology, head computed tomography, mild head trauma.